International Affairs and Canadian Migration Policy - Samy, Yiagadeesen; Duncan, Howard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
Yiagadeesen Samy is Director and Full Professor at the Norman Paterson School of International Affairs, Carleton University, Ottawa, Canada. Howard Duncan is Adjunct Research Professor, Department of Political Science, Carleton University; is Former Chair, Metropolis International Steering Committee; and is Former Editor, International Migration. This volume examines Canada$1 (Bs migration policy as part of its foreign policy. It is well known that Canada is a nation of immigrants. However, immigration policy has largely been regarded as domestic, rather than, foreign policy, with most scholarly and policy work focused on what happens after immigrants have arrived in this country. As a result, the effects of immigration to Canada on foreign affairs have been largely neglected despite the international character of immigration. The contributors to this volume underline the extent to which Canada$1 (Bs relationships with individual countries and with the international community is closely affected by its immigration policies and practices and draw attention to some of these areas in the hope that it will encourage more scholarly and policy activity directed to the impact of immigration on foreign affairs. Written by both academics and policy-makers, the book analyzes some of the latest thinking and initiatives related to linkages between migration and foreign policy. .s
Chapter 1: Introduction -- Chapter 2:The Political Foundations of Canadian Exceptionalism in Immigration Policy Chapter -- 3.Canada and the UN Global Compact on Refugees: A Case Study of Influence in the Global Refugee Regime -- Chapter 4:The Coming Clash Over Migration Policy Between Canada and the United States -- Chapter 5: Immigrants to Canada: Welcomed Citizens or Security Threats? -- Chapter 6. Canada$1 (Bs Position in the Global Competition for Talent -- Chapter 7: Weighing the Effects of Immigration on Canadian Prosperity: The Good, The Bad, and The Ugly -- Chapter 8: Sustainable Development and Diaspora Engagement in Canada -- Chapter 9:The Road Taken: Temporary Labour Migration in Canada$1 (Bs Immigration System Chapter 10: Cities of Migration: The Role of Municipal Planning in Immigrant Settlement and Integration -- Chapter 11:Managing Immigration in the Canadian Federation: The Case of Quebec -- Chapter 12:Conclusion: Will Canada$1 (Bs Immigration Policy Take an International Turn?s
Keywords: Political science; Globalization; Comparative politics; Emigration and immigration; Popular Science in Political Science and International Relations; Globalization; Comparative Politics; Migration